Construction of a pentacyclic ring system of isoryanodane diterpenoids by SmI2-mediated transannular cyclization. Issue 26 (28th June 2018) - Koshimizu, Masaki; Nagatomo, Masanori; Inoue, Masayuki
Abstract: Isoryanodane diterpenoids possess a densely oxygenated and intricately fused pentacycle (ABCDE-ring), although its unique ring system has not yet been assembled chemically. The 6/5/7-membered BCD-rings of isoryanodanes differ from the 5/6/6-membered rings of the structurally-related ryanodanes. We previously achieved the total synthesis of ryanodine and five other ryanodane diterpenoids by employing the common ABDE-tetracyclic intermediate 1 . Herein, we report a new strategy for constructing isoryanodane ABCDE-ring structure 3 from 1 via a combination of the oxy-Cope rearrangement and SmI2 -mediated transannular cyclization. Graphical abstract: Image 1